Development of gene-linked molecular markers in South African abalone (Haliotis midae) using an in silico mining approach - Rhode, Clint (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Genetics))--University of Stellenbosch, 2010.